Intellectual settlements in Ömer Seyfettin’s novella „The White Tulip” - Bas, Osman Firat (Balcanica Posnaniensia. Acta et studia, 2024)
The subject of this article is the novella The White Tulip by Ömer Seyfettin (1884–1920), one of the most important novelists of Turkish literature. The novella was published in 1914 and is set in Seres town occupied by the Bulgarians during the First Balkan War. In the article were made to reveal the meaning layer of the novella, in which the author, as an Eastern nationalist, reckons with the earlier manifestations of Eastern nationalism in Turkey. At a deeper layer, there are also the author’s reservations about the nationalist ideology of the Committee of Union and Progress, which began to take on an increasingly radical and racist character on the eve of the WWI. In this context, it seems as if two opposing tendencies coexisted in Seyfettin’s thought: on the one hand, he tries in The White Tulip to arouse a “national feeling” in the reader by means of very provocative images of violence, and on the other hand, to set moral boundaries for Turkish nationalism so that it does not take on a predatory character.